2017
DOI: 10.1186/s40793-017-0252-4
|View full text |Cite
|
Sign up to set email alerts
|

First draft genome sequence of a strain from the genus Fusibacter isolated from Salar de Ascotán in Northern Chile

Abstract: Fusibacter sp. 3D3 (ATCC BAA-2418) is an arsenate-reducing halotolerant strain within the Firmicutes phylum, isolated from the Salar de Ascotán, a hypersaline salt flat in Northern Chile. This high-Andean closed basin is an athalassohaline environment located at the bottom of a tectonic basin surrounded by mountain range, including some active volcanoes. This landscape can be an advantageous system to explore the effect of salinity on microorganisms that mediate biogeochemical reactions. Since 2000, microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…Sphingomonas genus comprises Gram-negative, chemoheterotrophic, strictly aerobic bacteria that are free-living in natural and man-made environments, including polluted and unpolluted sites [ 60 ]. Two additional genera were also identified in this sample, Fusibacter and Herbinix ; the first one has been isolated from oiled environments and has arsenate-reducing potential [ 61 , 62 ], while the second one comprises thermophilic cellulose-degrading bacteria [ 63 , 64 ]. Conclusively, this first approach to the indigenous microbial community of Domuyo revealed a rich and interesting environment which could host new and biotechnologically useful organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingomonas genus comprises Gram-negative, chemoheterotrophic, strictly aerobic bacteria that are free-living in natural and man-made environments, including polluted and unpolluted sites [ 60 ]. Two additional genera were also identified in this sample, Fusibacter and Herbinix ; the first one has been isolated from oiled environments and has arsenate-reducing potential [ 61 , 62 ], while the second one comprises thermophilic cellulose-degrading bacteria [ 63 , 64 ]. Conclusively, this first approach to the indigenous microbial community of Domuyo revealed a rich and interesting environment which could host new and biotechnologically useful organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Fusibacter (Phylum Firmicutes) was found in higher relative abundance in 20°C, 0.1 MPa, and oil‐contaminated incubations. Fusibacter has been previously described as a sulfur reducer at mesophilic Ts (Serrano et al, ). Type strain Fusibacter paucivorans has been isolated from an oil well (Ravot et al, ) and Fusibacter bizertensis from a kerosene tank (Smii et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2016) showed this may be the result of heterogeneous redox conditions forming within the sediment due to smothering by oil residues and the development of anoxic micro-niches. Fusibacter are generally halotolerant fermentative anaerobes capable of reducing a range of sulfur species and often isolated at mesophilic temperatures (Serrano et al, 2017). Several strains have been isolated from hydrocarbon related environments including the type strain Fusibacter paucivorans isolated from an oil-producing well (Ravot et al, 1999) and Fusibacter bizertensis isolated from a corroded kerosene storage tank (Smii et al, 2015).…”
Section: Bacterial Community Response Following Hydrocarbon Entrainmentmentioning
confidence: 99%